2017
DOI: 10.5812/modernc.11720
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Breast Cancer Screening in Nursing and Midwifery Personnel of Hospitals of Birjand, Iran

Abstract: Background: Breast cancer is the most common cancer in women and the fifth leading cause of cancer death worldwide. In developing countries, early diagnosis of breast cancer through available screening methods is the main strategy to reduce mortality. Objectives: This study aimed at investigating the barriers to breast cancer screening methods in nursing and midwifery personnel of hospitals of Birjand, Iran. Methods: In this cross sectional study, a total of 202 female nursing and midwifery personnel working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This finding suggested that high education level has a positive effect on health beliefs and behaviors. Safajou, Soltani, and Amouzeshi (2017) investigated the barriers of nurses and midwives in breast cancer screening and found that there was a significant relationship between age, marital status, education, and duty term and BSE and that having children increased BSE performance. However, in our study, it was found that the significant difference with the CHBMS sub-dimension scores was not due to the education level but the clinic where the nurses worked.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that high education level has a positive effect on health beliefs and behaviors. Safajou, Soltani, and Amouzeshi (2017) investigated the barriers of nurses and midwives in breast cancer screening and found that there was a significant relationship between age, marital status, education, and duty term and BSE and that having children increased BSE performance. However, in our study, it was found that the significant difference with the CHBMS sub-dimension scores was not due to the education level but the clinic where the nurses worked.…”
Section: Discussionmentioning
confidence: 99%